The genome of Magnolia hypoleuca provides a new insight into cold tolerance and the evolutionary position of magnoliids - Zhou, Luojing; Hou, Feixia; Wang, Li; Zhang, Lingyu; Wang, Yalan; Yin, Yanpeng; Pei, Jin; Peng, Cheng; Qin, Xiaobo; Gao, Jihai (Frontiers in Plant Science, 2023)
Magnolia hypoleuca, a member of the Magnoliaceae of magnoliids, is one of the most phylogenet-ically, economically, and important ornamental tree species widely grown and cultivated in Eastern China. In addition, M.hypoleuca lies in the anciently diverged magnoliid clade of angio-sperms, which has a controversial phylogenetic position relative to eudicots and monocots. We report a chromosome-scale assembly of the M.hypoleuca genome by combining Oxford Nanopore sequencing and Hi-C technologies. The 1.7 Gb assembly covers 96.64% of the genome which is distributed into 19 chromosomes, with contig N50 of 1.71 Mb and containing 33,873 annotated protein-coding genes. Phylogenetic analyses of 10 representative angiosperm genomes revealed that magnoliids were sister to the eudicots and monocots. Genomic comparisons between M.hypoleuca and other angiosperms suggesting the magnoliids are sister to the eudicots, rather than sister to monocots or both monocots and eudicots. M.hypoleuca was found to share a common ancestor with M.officinalis approximately 23.4 MYA, and the climate change of OMT (Oligo-cene-Miocene transition) is the main reason for the divergence of M.hypoleuca and M.officinalis, which was along with the division of Japanese islands. Moreover, the gene expansion observed in M.hypoleuca might contribute to the enhancement of cold tolerance and flower fragrance. The M.hypoleuca genome sequence not only represents a valuable resource for breeders, but also is important for clarifying the molecular mechanisms involved in cold tolerance and flower fragrance. These findings provide insights into the evolutionary history of M.hypoleuca and the relationships among the magnoliids, monocots, and eudicots, and enable us to delve into the fragrance and cold tolerance produced by them and offer a more robust understanding of how the Magnoliales evolved and diversified.